Effects Of High Dosage of Codeine - Containing Cough Syrup Administration on Some Biochemical Parameters of Liver in Albino Rats (Journal of Biochemistry, Microbiology and Biotechnology, 2021)
The study aimed to determine the effect of a high dosage of codeine-containing cough syrup administration on some biochemical parameters of the liver in albino rats. Codeine at 80 mg/kg/day, 160 mg/kg/day, 240 mg/kg/day, 320 mg/kg/day cough syrup were administered orally to albino rats for 21 days, biochemical parameters were analyzed for the activities of Alanine aminotransferase (ALT), Aspartate aminotransferase (AST), Alkaline phosphatase (ALP), Bilirubin, Total protein and Albumin. Results obtained revealed that a high dosage of codeine administration significantly increased plasma levels of alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP), bilirubin and albumin while it reduced total protein level when compared with the control rats. The study confirmed the risk of increased hepatotoxicity due to a high dosage of codeine administration. Although codeine is reported to be effective in pain management, its toxicity should be kept in mind.
Keywords: Codeine; Hepatotoxicity; Bilirubin; Aspartate aminotransferase; Alkaline phosphatase